2013
DOI: 10.1134/s0006297913130014
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A)-binding proteins: Structure, domain organization, and activity regulation

Abstract: RNA-binding proteins are of vital importance for mRNA functioning. Among these, poly(A)-binding proteins (PABPs) are of special interest due to their participation in virtually all mRNA-dependent events that is caused by their high affinity for A-rich mRNA sequences. Apart from mRNAs, PABPs interact with many proteins, thus promoting their involvement in cellular events. In the nucleus, PABPs play a role in polyadenylation, determine the length of the poly(A) tail, and may be involved in mRNA export. In the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 155 publications
0
76
0
2
Order By: Relevance
“…It was previously shown that PABP preferentially interacts with poly(A) or A-rich sequences (Eliseeva et al, 2013). The binding affinity increases as the A stretch gets longer (Eliseeva et al, 2013; Khanam et al, 2006; Kühn and Pieler, 1996; Sachs et al, 1987). Full-length PABP occupies an ∼25 nt A-tail as determined by nuclease digestion assay (Baer and Kornberg, 1983; Eliseeva et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that PABP preferentially interacts with poly(A) or A-rich sequences (Eliseeva et al, 2013). The binding affinity increases as the A stretch gets longer (Eliseeva et al, 2013; Khanam et al, 2006; Kühn and Pieler, 1996; Sachs et al, 1987). Full-length PABP occupies an ∼25 nt A-tail as determined by nuclease digestion assay (Baer and Kornberg, 1983; Eliseeva et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The binding affinity increases as the A stretch gets longer (Eliseeva et al, 2013; Khanam et al, 2006; Kühn and Pieler, 1996; Sachs et al, 1987). Full-length PABP occupies an ∼25 nt A-tail as determined by nuclease digestion assay (Baer and Kornberg, 1983; Eliseeva et al, 2013). In order to test an effect of PABP on uridylation, we carried out in vitro uridylation assays in the presence of recombinant PABPC1 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Within this segment of 8q22.2 is the gene PABPC1 , whose protein function is to bind the poly-A tail of messenger RNA (mRNA) in the nucleus and shuttle the transcript to the cytoplasm for translation (Eliseeva et al 2013). PABPC1-associated poly-A tails stimulate translation and stabilize mRNA in the cytoplasm and increased levels of PABPC1 may lead to excessive and oncogenic increases in the mRNA half-lives and thus increased potency of even a normal number of transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Newly synthesized mRNA is known to acquire a long poly(A) tail (up to ∼250 nucleotides [nt]) through canonical polyadenylation coupled to transcription, which facilitates mRNA export from the nucleus (Wahle and Keller 1996). In the cytoplasm, poly(A) tails are associated with cytoplasmic poly(A)-binding proteins (PABPCs) that stabilize mRNA by acting as a safeguard against multiple decay machineries and promote protein synthesis (Eliseeva et al 2013;Norbury 2013). Once mRNA is deadenylated to a certain threshold (∼25 nt), PABPC is released, and mRNA becomes translationally inactive and prone to degradation.…”
mentioning
confidence: 99%